A Bioinspired Tilt Sensor Model with Adaptive Gain and Enhanced Sensitivity. (27th April 2014) - Liu, Lijun; Lei, Ying
Abstract : Although various types of tilt sensors have been proposed in the past decade, it is still essential to develop rugged, cheap, simple-structured tilt sensors with wide measuring range and high sensitivities for efficient monitoring of infrastructures and early warning of natural disasters. It has been investigated that stereocilia in some fishes' inner ear organs are the basic sensory units of nature's inertial sensors and are highly sensitive over broad dynamic range because of a combination of adaptation and negative stiffness mechanisms. In this paper, a bioinspired tilt sensor model is proposed that mimics the mechanism of stereocilia in adaptive signal amplification to mechanical stimuli, leading to high sensitivity to weak input and low sensitivity to high input, thus expanding the dynamic range through adaptive amplification. The negative stiffness mechanism is implemented by magnet forces. The tilt motion is measured by the strain gauge at the end of the flexible cantilever beam element in the model. Measurements of both static and dynamics tilt motion are investigated. Numerical simulation results are used to demonstrate the capability of the proposed model for the measurements of tilt motions with adaptive amplification and enhanced sensitivity.